God against religion: rethinking Christian theology through worship - Boulton, Matthew Myer (The Calvin Institute of Christian worship liturgical studies series, 2008)
Introduction: Rethinking theology -- Through worship in the reformed tradition -- The invention of God -- Karl Barth on worship as "fall" -- The work of "religion" -- The creation of Eve -- Revelation, idolatry, and the Holy Spirit -- Rereading Genesis 2-4 -- Eden and intimacy -- Leitourgia and separation -- Religion and murder -- "We pray by His mouth" -- Karl Barth on worship as "reconciliation" -- The work of human being -- The work of gratitude -- Conspiracy and solidarity -- Martin Luther and Christian life -- Martin Luther's simul -- Penitential life -- Baptismal life -- God against religion -- A theology of invocation -- The end of Christianity -- The play of redemption -- Postlude : Reforming worship -- "No difference at all" -- "All the difference in the world" -- Christian Baptism -- Christian Communion